Ceramic microlattice and epoxy interpenetrating phase composites with simultaneous high specific strength and specific energy absorption - Li, Xinwei; Kim, Minseo; Zhai, Wei (Materials & design, 2022)
[Display omitted] •Alumina truss-microlattice and epoxy-infilled interpenetrating-phase composites.•High strength and long plateau stress for energy absorption.•Enhanced toughness of alumina when embedded in the epoxy.•Synergistic co-reinforcement in strength of the two phases. Being lightweight, strong, and tough, are qualities often sought-after in practical engineering materials. Herein, we present interpenetrating phase composites (IPC), based on the combination of additively manufactured alumina microlattices and infiltrated epoxy, that display an excellent combination of such characteristics. Experimental and simulation studies on the compressive behaviours of different truss-microlattices and their functionally-graded variants have been carried out. Lengthened stress plateau up to −0.6 strain and co-enhanced strength up to 65 % higher than the linear sum of their constituents have been observed. This constitutes a simultaneous high specific strength and specific energy absorption up to 113.5–142.6 MPa/(g/cm3) and 25.3–35.6 J/g, respectively, for the IPCs, at low densities of around 1.8 g/cm3. The mechanism of the co-enhanced strength attribute to the improved alumina fracture toughness whilst the lengthened plateau attributes to the progressive material failure and strain energy relaxation. Overall, this work demonstrates the potential of using a strong ceramic and epoxy to achieve simultaneously high specific strength and energy absorption.